(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Globally breast cancer is the most common deadly cancer and major health problem in women. Recurrence of breast cancer is a major clinical manifestation and represents the principal cause of breast cancer related deaths. During diagnosis most of the breast cancer patients are detected and treated in a curative state with some patient’s experiences recurrence following completion of treatment after a certain period. Therefore, explore the associated factors related to recurrence of breast cancer would be helpful in estimating the treatment outcomes and predicting the prognosis. This study aimed to evaluate the factors related to recurrences and post recurrent mortality for five years after primary treatment among breast cancer patients. Materials and methods: In this prospective cohort study on patients selected between 2014-2016 who developed recurrence after primary treatment of breast cancer, they were evaluated, treated and followed up for five years from the primary treatment. Data was compiled as age, molecular subtypes, type of operation, margin status, treatment status, sociodemographic profile. Death was analyzed considering the time period, age of the patient and molecular profile of the tumor. Kaplan-Meier methods were used for survival estimation and for comparing mean survival among different groups, the Log-Rank test was utilized. Results: Mean age at the time of primary treatment was 41.6 years, 55.7% was below 40 years of age, 78.7% had mastectomy, 21.6% underwent an unplanned lumpectomy, margin positivity was noticed in 17% of cases, 34% failed to receive axillary surgery. Regarding treatment status, 71% received incomplete treatment (p=.049) and larger tumor-17% (T3+T4) had more recurrences (p=.05). Out of 86 informed cases 59 died (68.6%) within five years of primary treatment. More death was noticed in younger and hormone negative groups. Highest survival was seen in the HR+veolder group and increased survival in younger ages demonstrated by Kaplan-Meier curve. Conclusion: Incomplete treatment is an associated factor apart from younger age and molecular factors for recurrence in breast cancer treatment. Recurrence is an important risk factor for poor survival after breast cancer treatment. JCMCTA 2024 ; 35 (1) : 147-154